Considerations on a series of meningeal subarachnoidal hemorrhages in children above the neonatal period - Giraud, P.; Paillas, J.E.; Orsini, A.; Righini, Cl. (The Turkish Journal of Pediatrics, 1963)
Our understanding of meningeal subarachnoidal hemorrhage has undergone considerable change in the last twenty years. Formerly, the diagnosis of meningeal hemorrhage was considered an end in itself, on a par with cerebral softening or hemorrhage. Aside from cases of arterial hypertension of the newborn and certain well known blood diseases, its etiology remained uncertain and more than half of the meningeal hemorrhages of adolescence or young adulthood were classified as «idiopathic». Now, however, thanks to modern techniques of investigation, such as electroencephalography and angiography, the majority of the so-called idiopathic hemorrhages have been assigned a cause: vascular malformations, arterial aneurysms or arteriovenous angiomas, sufficient to account for the bleeding. Among adults, all authors agree, such malformations account for 50 per cent of meningeal hemorrhages. However, few recent works have been devoted to the meningeal hemorrhages of children, apart from those of the early neonatal period. It is therefore to this phase of nervous system pathology of childhood that we have dedicated this work. We have collected fifteen cases of children who presented a clinical picture of meningeal hemorrhage and in whom lumbar puncture revealed bloody cerebrospinal fluid. We included all the children whose major original symptoms were meningeal and in whom bloody cerebrospinal fluid was found but we excluded patients who, at the onset, presented a clinical picture of cerebral hemorrhage even though the hemorrhage later became cerebromeningeal.